Analisis Gaya Kepemimpinan Dan Pemberian Kompensasi Dalam Meningkatkan Kinerja Pegawai Ditinjau Dari Perpektif Islam: Studi Kasus Pada Biro Pemerintahan Dan Otda Setdaprovsu Bagian Tata Usaha - Fadiya Maysaroh Lubis (Jurnal Akuntansi AKTIVA, 2023)
This research uses a qualitative approach. In its research approach method, this research is more directed to case studies. The primary data taken by the researcher this time was by interviewing several employees/staff in the administration sub-section. The author uses descriptive data analysis techniques by analyzing all data obtained from various available sources. Researchers also perform data analysis techniques by reducing data, presenting data, and drawing conclusions on the issues raised. From this study, there are results which show that in the Office of the Governor of North Sumatra, the Government Bureau and Regional Autonomy Secretariat, the Administration section shows that in these agencies the leader applies a participatory leadership style model. It can be seen from the results of the interviews that have been conducted, that is, when one of the staff is facing a problem that could interfere with their performance, the leader immediately gives personal encouragement, the leader also has leadership standards, can protect employees and be friends with them, often coordinates with employees. Employees are also responsible for their actions. Compensation in the Office of the Governor of the Government Bureau and Otda Setdaprovsu administration section, there are various kinds of compensation here, namely in the form of direct and indirect compensation, such as: monthly salary/wages, TPP, study tour/out of town service, and Satya badges.